Organophosphate Poisoning Simulation - Maria Sheakley; Richard Lammers; John Hoyle Jr (Association of American Medical Colleges, 2015)
Abstract This resource is a high-fidelity simulation case on organophosphate poisoning. It follows a 40-year-old adult male with complaints of dimmed vision, watery eyes, shortness of breath, nausea, vomiting, diarrhea, and sweating. The simulation uses a manikin and includes all the necessary materials for learners to complete the scenario. The case is intended to teach teamwork and clinical skills in a realistic emergency department setting, with an underlying emphasis on the physiology of the autonomic nervous system. Students should be able recognize the signs and symptoms of organophosphate poisoning, and select the appropriate personal protective gear for the situation. They should also be able to assign roles to group members, and address the basic airway, breathing, and circulation on the simulated patient. This simulation was used for first-year medical students. The students had a few introductory lectures on the autonomic nervous system and autonomic drugs prior to the simulation event. This was crucial for the students to be able to recognize the autonomic signs and symptoms the simulated patient is exhibiting, and know what to use for treatment. In addition, all of the students had previously completed a Medical First Responders course, which utilized high-fidelity simulators. Due to this training, the students were familiar with basic medical terminology, teamwork as medical professionals, basic first response care, the high-fidelity simulators, and the use of personal protective equipment.